2009
DOI: 10.30539/iraqijvm.v33i2.700
|View full text |Cite
|
Sign up to set email alerts
|

Detection of trihalomethane (chloroform) in drinking water in Baghdad city

Abstract: This study designed to determine the chloroform concentration in drinking water in Baghdad city. Thechloroform concentration specified into drinking wter into four portions per a week along two weeks in eachmonth for three months of this study (August, October and December) , 2008 each portion has two samples,so the total number be 48 drinking water samples (sixteen samples per month as an equal portions for eachproject and district).Four projects of water supply filtration stations were selected in Baghdad ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Twelve studies were conducted in the United States [ 19 21 , 24 , 26 , 66 , 72 75 , 80 , 84 ], nine in Nigeria [ 57 , 59 , 68 , 76 – 78 , 83 , 88 , 94 ], five in Turkey [ 58 , 70 , 79 , 85 , 89 ], four in China [ 91 93 , 96 ], three in India [ 61 , 65 , 69 ], two in Saudi Arabia [ 82 , 95 ], two in Russia [ 86 , 87 ], two in Germany [ 62 , 63 ], one study in each other countries, such as Poland [ 60 ], Venezuela [ 90 ], Spain [ 67 ], Sudan [ 99 ], Singapore [ 102 ], Iraq [ 100 ], Serbia [ 97 ], United Kingdom [ 98 ], Iran [ 101 ], Malaysia [ 71 ], Italy [ 64 ], Sweden [ 22 ], and Pakistan [ 81 ]. The follow-up duration of cohort studies ranged from seven to about 28 years [ 20 , 26 , 66 ,…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Twelve studies were conducted in the United States [ 19 21 , 24 , 26 , 66 , 72 75 , 80 , 84 ], nine in Nigeria [ 57 , 59 , 68 , 76 – 78 , 83 , 88 , 94 ], five in Turkey [ 58 , 70 , 79 , 85 , 89 ], four in China [ 91 93 , 96 ], three in India [ 61 , 65 , 69 ], two in Saudi Arabia [ 82 , 95 ], two in Russia [ 86 , 87 ], two in Germany [ 62 , 63 ], one study in each other countries, such as Poland [ 60 ], Venezuela [ 90 ], Spain [ 67 ], Sudan [ 99 ], Singapore [ 102 ], Iraq [ 100 ], Serbia [ 97 ], United Kingdom [ 98 ], Iran [ 101 ], Malaysia [ 71 ], Italy [ 64 ], Sweden [ 22 ], and Pakistan [ 81 ]. The follow-up duration of cohort studies ranged from seven to about 28 years [ 20 , 26 , 66 ,…”
Section: Resultsmentioning
confidence: 99%
“…The follow-up duration of cohort studies ranged from seven to about 28 years [ 20 , 26 , 66 , 74 ]. In 36 studies, prostate cancer was confirmed by a histopathological examination [ 19 , 20 , 22 , 24 , 26 , 57 59 , 61 64 , 67 69 , 71 74 , 76 – 78 , 80 , 82 89 , 92 , 97 , 100 102 ]; in two studies it was confirmed by prostate-specific antigen (PSA) test [ 81 , 94 ], and in one study it was confirmed by clinical data and current international clinical staging method [ 93 ]. In other 13 studies, prostate cancer diagnosis method was not described [ 21 , 60 , 65 , 66 , 70 , 75 , 79 , 90 , 91 , 95 , 96 , 98 , 99 ] ( Table 1 and S2 Table ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[20]. [21] revealed that the free chlorine in drinking water was below the standards set by the World Health Organization (WHO) in the period from July up to the end of August 2007. Some variables that affect drinking water, such as the amount of free chlorine, temperature, pH, and the oxidation-reduction potential of water on the sanitising efficiency of chlorine, have been studied and found to follow the same trend as [22].…”
Section: Table (2): Concentration Of Cadmium In the Blood Of Human An...mentioning
confidence: 99%